Improvement Quality of Software Requirements Using Requirement Negotiation System for Supporting Decision - Egia Rosi Subhiyakto; Yani Parti Astuti (JUITA : Jurnal Informatika, 2022)
The Requirement Engineering phase, where all requests and software requirements of the user and the client are delivered, understood and agreed upon. However, often the developers are just too focused on implementing the software, even though the Requirements Engineering phase is a phase that can have a big impact. The impact is not only on the final product but also on the development process itself. In this study, the authors conducted software development negotiation of software requirements as a medium for stakeholders to negotiate the requirements of software products. In the negotiation system, the author will provide a means of decision support or group decision support system that a method of resolving conflicts. The main objectives of this work are twofold: 1) to assist the negotiation process between stakeholders and 2) to improvement quality software after negotiation. The workings of the E-Voting method are by giving choices to each sub-specification that has been chosen by stakeholders. We will select the choice that has the highest number of votes as a specification. We used prototyping as a method of developing a system life cycle because prototyping is very open to improvements that might occur after it releases the prototype version system. The results of evaluations show that the system has a high success rate based on 3 dimensions of testing, Performance (80.5%), Usability (78.5%), and User Satisfaction (78%).